PENGARUH PERTUMBUHAN LABA, KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Sri Dewi Ayu Safitri; Mohamad Kamal Reza; Nurmalasari Nurmalasari (STIE 'INDONESIA' Pontianak, 2023)
The company's main goal is to pay attention to the welfare of the company's owners by optimizing the value of the company. Firm value is a picture of the state of a company, where there is a special assessment by potential investors of the good and bad financial performance of the company. Every company owner tries to give a good signal to the public about the value of the company. This is done by the company to obtain external capital to increase production activities. This research was conducted on LQ45 companies listed on the Indonesia Stock Exchange in 2014-2018 as many as 65 companies. The sampling technique in this study was taken based on the probability sampling method. The discussion uses descriptive analysis, classical assumption test, model selection test, and hypothesis testing. The test was carried out using Eviews 10. The results showed that the Profit Growth Ratio had an effect on Firm Value, Leverage Ratio (debt ratio) had no effect on Company Value, and Fata had no effect on firm value and Size Ratio had no effect on firm value.